STUDENTS’ PERCEPTION ON FACTORS AFFECTING ENGLISH LEARNING MOTIVATION OF STUDENTS IN STRATEGIC MISSION PROJECT AT ULIS, VNU - Nguyễn, Nhuệ Giang (2020)
Since 2009, first-year students in the Strategic Mission Project of Vietnam National University, Hanoi have emerged as a new group of students studying English as non-majors at University of Languages and International Studies (ULIS). Very different from other groups of students at the university in terms of their goals and objectives as well as their needs, they call for careful consideration and serious research. Being one of the first to investigate this under-researched population, this study looks at English learning motivation as reported by the students themselves. By employing survey questionnaires and semistructured interviews, the researcher wishes to find out the types of motivation the students possess, their changes in motivation while studying in the program and most importantly, the factors that have resulted in such changes. Analysis of data collected among 144 students with low English proficiency at the beginning of the school year has revealed that those students are very much career-oriented and urged to study by the pressure of examinations.